Ovarian Clear Cell Carcinoma: From Morphology to Molecular Biology. Issue 9 (October 2019) - Improta, Giuseppina; Pettinato, Angela; Høgdall, Estrid; Santeusanio, Giuseppe; Vatrano, Simona; Fraggetta, Filippo; Zannoni, Gian Franco
Abstract : Ovarian clear cell carcinoma (oCCC) is a distinctive subtype of ovarian carcinoma, with peculiar genetic and environmental risk factors, precursor lesions, molecular events during oncogenesis, patterns of spread, and response to treatment. Because of low response to chemotherapy and poor prognosis in advanced stages, there is growing interest in investigating the molecular pathways involved in oCCC development, in order to individualize novel/molecular targeted therapies. Until now, the main molecular genetic changes associated with oCCC remain to be identified, and, although several molecular changes have been reported in clear cell tumors, most studies have analyzed a limited number of cases; therefore, the true prevalence of those changes is not known. The present review will present the clinicopathologic features of oCCC, from morphology to molecular biology, discussing the diagnostic and treatment challenges of this intriguing ovarian carcinoma.